Carboxymethyl κ/ι-hybrid carrageenan doped with NH4I as a template for solid bio-electrolytes development - Torres F.G. (2019)
In this study, we analyzed the contribution of NH4I and glycerol on the ionic conductivity of carboxymethyl κ/ι-hybrid carrageenan-based solid bio-electrolytes. Electrochemical impedance spectroscopy was used to assess the electrochemical properties of the developed biopolymeric films and their interfaces over a wide range of frequencies (1& Hz–7& MHz). X-ray diffractograms demonstrated the increment of the amorphous fraction in the material as the NH4I content increases, suggesting an enhancement of ion transport processes and the successful incorporation of the salt into the host matrix.